2017
DOI: 10.1172/jci.insight.90380
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human trial of multikinase VEGF inhibitor regorafenib and anti-EGFR antibody cetuximab in advanced cancer patients

Abstract: BACKGROUND. The combination of multikinase VEGF inhibitor regorafenib and anti-EGFR antibody cetuximab overcomes intrinsic and acquired resistance in both EGFR-sensitive and EGFR-resistant preclinical models of colorectal cancer (CRC). METHODS.Utilizing a standard 3+3 design, a phase I study was designed to determine safety, maximum tolerated dose (MTD), and dose-limiting toxicities (DLTs) of the regorafenib plus cetuximab combination among patients with advanced cancer including CRC. Comprehensive genomic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…17%, respectively) . Notably, although a DLT of grade 3 thrombocytopenia was reported with regorafenib plus cetuximab in the trial by Subbiah et al ., only one case of grade ≥3 platelet count decrease was reported in our study, which was observed in the context of fatal liver failure and disseminated intravascular coagulation.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…17%, respectively) . Notably, although a DLT of grade 3 thrombocytopenia was reported with regorafenib plus cetuximab in the trial by Subbiah et al ., only one case of grade ≥3 platelet count decrease was reported in our study, which was observed in the context of fatal liver failure and disseminated intravascular coagulation.…”
Section: Discussioncontrasting
confidence: 71%
“…A recently published phase 1 combination trial by Subbiah et al ., of regorafenib plus cetuximab in 27 patients with advanced cancer refractory to several lines of therapy, described a considerably lower dose (regorafenib 80 mg QD plus cetuximab 200 mg/m 2 loading dose, followed by cetuximab 150 mg/m 2 weekly) as the MTD . At this dose, no DLTs were observed in the 19 evaluable patients; however, two DLTs (grade 3 thrombocytopenia in a patient with glioblastoma and grade 3 intra‐abdominal bleeding in a patient with CRC) were reported in five evaluable patients at the higher dose of regorafenib 120 mg QD plus cetuximab 200 mg/m 2 loading dose followed by 150 mg/m 2 weekly.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, the usage of bevacizumab induces the ECM remodeling which promote the drug delivery (Rahbari et al, ). Recently, the combination of multikinase VEGF inhibitor regorafenib and anti‐EGFR antibody cetuximab show a promising results in CRC treatment (Subbiah et al, ). Jung et al () indicated that through blocking ROS‐mediated VEGFR2 signaling pathways in endothelial cells (ECs), VEGF‐dependent angiogenesis was suppressed both in vitro and in vivo.…”
Section: Ros Role In Crc Microenvironment and Therapymentioning
confidence: 99%
“…In this respect, an exceptional response to regorafenib was reported in a patient with metastatic colorectal cancer and a mutation in the KDR gene encoding for VEGFR2 (32). This patient had an ongoing PR for over 9 months at the time of the report, despite being able to tolerate only a reduced dose of 40 mg. Another prolonged PR of 15 months as well as SD for over 20 months were observed in two patients participating in a phase I trial of the combination of regorafenib with cetuximab (33). Disease in both patients had previously progressed on each drug alone.…”
Section: Discussionmentioning
confidence: 89%